Incentives for Green Consumers on the Liberalised Energy Market of Romania in the Context of the Transition to Green Economy - È˜erbÄƒnescu, Ana (International Journal of Energy Economics and Policy, 2021)
The liberalisation process of energy markets has been progressing since 1990 and starting 2012 it has also begun in Romania, being finalised in January 2021 and granting the household consumers the possibility to choose an energy supply company. Together with the context of an ongoing transition towards a green economy, it is important to analyse and understand the criteria of consumers when choosing their energy supplier in order to design appropriate policies which will ensure the success and efficiency of the transition. This research targets the household consumers of Romania and the methodology consists of a questionnaire, whereas the data gathered was analysed using SPSS. The first hypothesis, of a correlation between the income of the consumer and the willingness to pay additionally for renewable energy, was not validated. Therefore, an increased standard of living does not translate to the willingness of consumers to invest in green energy. However, the second hypothesis, of an association between the level of education and the criteria of the consumers when they choose an energy supplier, was validated, indicating that the incentive in changing the criteria of consumers is to work together for the green economy transition and to develop a stronger educational background. Keywords: household consumers, greeen economy, energy market, liberalisation, consumer behaviour, education level JEL Classifications: A19, P18, O44 DOI: https://doi.org/10.32479/ijeep.11720